Accounting Student's Engagement in Hybrid Learning Environment - Laily, Nujmatul; ., Sulikah; Herdiani, Aulia; Ardhani, Lutfi (KnE Social Sciences, 2024)
Hybrid learning is an alternative learning that can provide wider access for students to learn and increase student’s participation in learning. Student’s involvement in the hybrid learning model is an interesting and important issue to be researched. This study aims to examine whether there are differences in cognitive engagement, emotional engagement, social engagement, behavioral engagement, and collaborative engagement in hybrid learning. This research is an experimental research. A total of 52 accounting students participated in the research respondents were given treatment in the form of implementing hybrid learning. The t-test is used to determine whether there is differences in social engagement, cognitive engagement, emotional engagement, behavioral engagement, and collaborative engagement in hybrid learning. The results show that student engagement is different before and after the implementation of hybrid learning based on the five dimensions of engagement. Educators who intend to increase student engagement can use hybrid learning. Keywords: engagement, hybrid learning, accounting, participation